2009
DOI: 10.3390/molecules14051808
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial Activity of Six Pomegranate (Punica granatum L.) Varieties and Their Relation to Some of Their Pomological and Phytonutrient Characteristics

Abstract: Arils from six pomegranate (Punica granatum L.) varieties grown in the Mediterranean region of Turkey were tested for their antimicrobial properties by the agar diffusion and minimum inhibitory concentration (MIC) methods against seven bacteria: (Bacillus megaterium DSM 32, Pseudomonas aeruginosa DSM 9027, Staphylococcus aureus Cowan 1, Corynebacterium xerosis UC 9165, Escherichia coli DM, Enterococcus faecalis A10, Micrococcus luteus LA 2971), and three fungi (Kluvyeromyces marxianus A230, Rhodotorula rubra M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
84
2
5

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 140 publications
(100 citation statements)
references
References 25 publications
(31 reference statements)
7
84
2
5
Order By: Relevance
“…1 As shown by the MICs in Table 5, the ethanol extracts generally showed higher antibacterial and antifungal activities and were active against more of these species than the water extracts. The positive results of antimicrobial activities against E. coli, L. monocytogenes, P. auroginosa, S. aureus, C. albicans and A. fumigatus are in accordance with the literature (54)(55)(56). The ethanol extracts of the exocarp and mesocarp showed the lowest MICs against C. albicans, C. parapsilosis, R. mucilaginosa, E. dermatitidis and S. aureus.…”
Section: Antibacterial and Antifungal Activitiessupporting
confidence: 89%
“…1 As shown by the MICs in Table 5, the ethanol extracts generally showed higher antibacterial and antifungal activities and were active against more of these species than the water extracts. The positive results of antimicrobial activities against E. coli, L. monocytogenes, P. auroginosa, S. aureus, C. albicans and A. fumigatus are in accordance with the literature (54)(55)(56). The ethanol extracts of the exocarp and mesocarp showed the lowest MICs against C. albicans, C. parapsilosis, R. mucilaginosa, E. dermatitidis and S. aureus.…”
Section: Antibacterial and Antifungal Activitiessupporting
confidence: 89%
“…The antibacterial, antiparasitic, antiviral, antioxidant, and anti-inflammatory effects have been reported for pomegranate peel (Bekir, 2013;Duman et al, 2009;Tayel & El-Tras, 2010). Also, the plant can minimize the problem of antibiotic resistance of H. pylori by increasing the cell surface hydrophobicity of H. pylori strains and inhibiting the attachment of the bacterium to the gastric mucosa (Voravuthikunchai et al, 2006).…”
Section: Punica Granatummentioning
confidence: 99%
“…Pomegranate fruit extracts/constituents possesses immense biological activities such as anticarcinogenic (Whitley et al, 2003;Afaq et al, 2005), antibacterial (Akiyama et al, 2001;Prashanth et al, 2001;Duman et al, 2009), antidiarrhoeal (Das et al, 1999), antifungal (Dutta et al, 1998), antiulcer (Gharzouli et al, 1999), antioxidant activity and free radical scavenging capability (Schubert et al, 1999;Aviram et al, 2000;Festa et al, 2001), strengthening of the immune system , prevention of heart disease (Johanningsmeier & Harris, 2011) and liver fibrosis (Thresiamma & Kuttan, 1996), and inhibition of lipid peroxidation even at lower concentrations than vitamin E . All these therapeutical activities are related to the presence of diverse 'phenolic compounds', including gallic acid, protocatechinunic acid, chlorogenic acid, caffeic acid, ferulic acid, coumaric acid, and catechin and hydrolysable tannins (such as punicalin, pedunculagin, punicalagin, corilagin, casuarinin, punicacortein, granatin and ellagic acid), and anthocyanins (delphinidin, cyanidin and pelargonidin 3-glucosides and 3,5-diglucosides) (Amakura et al, 2000;Noda et al, 2002;Poyrazoglu et al, 2002;Kulkarni & Aradya, 2005;Viuda-Martos et al, 2010).…”
Section: Wwwintechopencommentioning
confidence: 99%
“…Food-borne illnesses are still an important concern for both consumers, the food industry and food safety authorities, thus, the ongoing search for natural antimicrobials for prevention of food-borne illnesses is a vast exploring area for scientists. Antimicrobial activities of pomegranate have been studied by some researchers and the extent of inhibitory effect is always attributed to the pomegranate antioxidant activity that depends mainly on the phenolic and anthocyanin content of the fruit (Holetz et al, 2002;Braga et al, 2005;Mathabe et al, 2006;McCarrell et al, 2008;Al-Zoreky, 2009;Duman et al, 2009;Gould et al, 2009;Parashar et al, 2009;Panichayupakaranant et al, 2010, Orak et al, 2011. In a previous study, Opara et al (2009) reported that the best activity against Staphyloccocus aureus and Pseudomonas aeruginosa were found in fruit peel compound punicalagin, particularly from Oman, which was coincident with the highest levels of vitamin C detected in these samples.…”
Section: Antimicrobial Propertiesmentioning
confidence: 99%